2020
DOI: 10.33457/ijhsrp.765438
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Nursing Care in Cases Requiring Emergency Surgery in Covid-19 Infected Patients

Abstract: Covid-19 which emerged in Wuhan, China in December 2019, is an infectious disease caused by coronavirus and causes serious respiratory infections. The Covid-19 disease was declared as a pandemic by the World Health Organization in March 2020 due to its easy and rapid spread and affecting many countries globally. This rapid spread also increased the number of individuals infected with the virus worldwide. Unfortunately, deaths resulting from the disease cannot be prevented and the number of individuals who lost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Previous studies reported that RNs have play important roles in assessing, diagnosing, planning, intervening, and evaluating to ensure patients’ comfort [ 8 ]. In addition, RNs contribute significantly to prevent the risk of contamination during surgical interventions, particularly infection due to anesthesia equipment and oxygen consumables [ 9 ]. In this study, Competency in the nursing process refers to RNs have confidence in their knowledge, skills, and attitude to implement the five steps of the nursing process with individual patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that RNs have play important roles in assessing, diagnosing, planning, intervening, and evaluating to ensure patients’ comfort [ 8 ]. In addition, RNs contribute significantly to prevent the risk of contamination during surgical interventions, particularly infection due to anesthesia equipment and oxygen consumables [ 9 ]. In this study, Competency in the nursing process refers to RNs have confidence in their knowledge, skills, and attitude to implement the five steps of the nursing process with individual patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%